Ultrasound in acute cholecystitis - Olascuaga, Carlos; Borgno, Laura; González, Fernando (Cirugía del Uruguay, 2001)
Review of 100 cases of patients treated from January 1996 through Ju/y 1998 at the emergency unit of Pasteur Hospital, cho/ecystectomized and having clinico-ultrasound andlor anatomo-pathologic diagnoses of acule cholecystitis.